Assessment of knowledge and compliance to evidence-based guidelines for VAP prevention among ICU nurses in Tanzania - Vicent Bankanie; Anne H. Outwater; Li Wan; Li Yinglan (BMC, 2021)
Abstract Background Implementation of evidence-based guidelines (EBGs) related to VAP is an effective measure for the prevention of ventilator-associated pneumonia (VAP). While low knowledge regarding the EBGs related to VAP prevention among ICU nurses is still a major concern among nurses in ICUs globally, the situation in Tanzania is scarcely known. This study aimed to assess the ICU nurses' knowledge, compliance, and barriers toward evidence-based guidelines for the prevention of VAP in Tanzania. Methods A cross-sectional study, involving ICU nurses of major hospitals in Tanzania, was conducted. A structured questionnaire was administered among 116 ICU nurses. Data analysis included descriptive statistics and the independent sample t-test. Results The mean knowledge score was 3.86(SD = 1.56), based on ten questions (equivalent to 38.6%). Nurses with a degree or higher level of nursing education performed significantly better than the nurses with a diploma or lower level of nursing education (p = 0.004). The mean self-reported compliance score for EBGs for the prevention of VAP was 15.20 (SD = 0.93) which is equivalent to 60.8% based on 25 questions. The main barriers to the implementation of EBGs for VAP prevention were lack of skills (96.6%), lack of adequate staff (95.5%), and lack of knowledge (79.3%). Conclusion Considering the severity and impact of VAP, and the higher risks of HAIs in resource-limited countries like Tanzania, the lower level of knowledge and compliance implies the need for ongoing educational interventions and evaluation of the implementation of the EBGs for VAP prevention by considering the local context.